The relationship between mobile broadband usage and user mobility with lockdown restrictions in Spain. - García-Manrique-Ocaña, José Manuel; Marcenaro-Gutiérrez, Óscar David; López-Agudo, Luis Alejandro (Taylor & Francis, 2022)
This paper studies how COVID-19 lockdown restrictions encouraged and allowed people to form habits ofincreased mobile phone usage in Spain, even after the most restrictive measures were lifted. We have useddata from the mobile network of a national telecommunications operator to study the inﬂuence of 15different mobility restrictions on citizens’ use of mobile phones from 15 March 2020 to 15 April 2021 ina big Spanish city. In order to approach this issue, a quasi-experimental technique (before and aftermethodology) was implemented. We found that the use of smartphones presented an initial reductionwith the ﬁrst and most drastic mobility restrictions, but showed a growing use after their removal.However, user mobility was negatively inﬂuenced by all the mobility restrictions.
Keywords: COVID-19 - Política gubernamental; Internet - Aspectos sociales; Movilidad geográfica; Confinamiento (Política sanitaria); COVID-19; Mobility; Internet use; Lockdown; Government restrictions